KAJIAN MODIFIKASI BOTTOM OUTLET BENDUNGAN BUDONG-BUDONG KABUPATEN MAMUJU TENGAH, SULAWESI BARAT - Albi Daniel Hasudungan; Kresno Wikan Sadono (Racic : Rab Construction Research, 2025)
This study evaluates the outlet system design for the Budong-Budong Dam, with a focus on optimizing downstream water delivery for irrigation purposes, calculated at 410 liters per second. The outlet structures are categorized by their discharge pathways: river outlet channels, channel outlet channels, and pressurized pipe outlets. A bottom outlet is proposed to aid in meeting irrigation demands, with hydraulic analysis conducted to determine the optimal diameter for efficient water flow. Two diameters (0.4 m and 0.6 m) were analyzed for total head loss, factoring in head loss from the trash rack, entrance, and friction. Results show that a 0.4 m diameter produces a head loss of 4.2905 m, while a 0.6 m diameter produces a head loss of 1.8599 m, consistent with Bernoulli’s Principle that smaller cross-sectional areas increase head loss. Both diameters meet the required downstream discharge of 0.705 m³/s, with head loss remaining within safety limits across hollow jet valve openings. The study concludes that both diameters are feasible for downstream discharge requirements, with the installation of the bottom outlet coordinated in parallel with diversion tunnel excavation for project efficiency.